The Fate of 131I-17-lodohepta-decanoic Acid During Lactate Loading: Its Oxidation is Strongly Inhibited in Favor of its Esterification - Duwel, C. M. B.; Visser, F. C.; van Eenige, M. J.; Den Hollander, W.; Roos, J. P. (Nuklearmedizin - NuclearMedicine, 1990)
The influence of lactate loading on fatty acid metabolism (pH = 7.4) by the normal canine heart was investigated radiochemically using the radioiodinated fatty acid 131I-17-iodoheptadecanoic acid (131I-17-HDA). Fatty acid metabolism was studied during control conditions (n = 8) and after lactate loading (n = 7). In the canine heart total myocardial131I-17-HDA radioactivity (uptake) was not changed during the lactate intervention. The oxidation decreased fivefold (measured as free 131I-iodide ion) from 70% to 14% (p < 0.0001, Student’s t- test). Thin-layer chromatography of cardiac lipids demonstrated that the nonoxidized 131I-17-HDA was mainly stored in the triglycerides and phosphoglycerides. These results suggest that lactate inhibits cardiac 131I-HDA oxidation.Der Einbau von 131J-17-Jod-Hepta- dekansäure (131J-17-HDA) wurde am gesunden Hundeherz unter Kontroll- bedingungen (n = 8) und nach Zugabe von Laktat (n = 7) untersucht. Der Gesamtwert der myokardialen 131J-17- HDA-Aufnahme war unter Laktatinfusion unverändert. Die Oxidation verringerte sich um das Fünffache (gemessen am freien 131J-Jodid), nämlich von 70 auf 14% (p <0,0001). Die Dünnschicht-Chromatographie der myokardialen Lipide zeigte, daß nicht- oxidierte 131J-17-HDA hauptsächlich in Triglyzerid und die Phosphorglyzeride eingebaut wurde. Diese Ergebnisse weisen auf eine Laktat-vermittelte Inhibition der Oxidation von 131J-17- HDA hin.